Pemantauan dan Deteksi Dini Risiko Anemia pada Ibu Hamil dan Stunting Balita melalui Pemeriksaan Antropometri di Puskesmas Kuranji Kota Padang - Arif Rohman Mansur; Dwi Novrianda; Mutia Farlina; Meri Neherta; Lili Fajria; Deswita Deswita; Yelly Herien; Wedya Wahyu; Ira Mulya Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Stunting and anaemia in pregnant women are global conditions that are interrelated with the risk of declining health status in children and pregnant women. Anaemia in pregnant women poses a risk of stunting in children, impacting growth and development, brain function, immune system, and learning abilities. For this reason, the purpose of community service is to detect the early risk of stunting in children and anaemia in pregnant women. The method used is an anthropometric examination of toddlers and pregnant women using weight, height, upper arm circumference, and haemoglobin examination to detect the risk of stunting and anaemia. Inspection and measurement data were processed using KMS online and SPSS and presented descriptively in frequency distribution tables and central tendency values. This activity was carried out at the Durian Tiga Batang Posyandu, Kuranji Health Center, Padang City, on 10 August 2023. Data was collected on 50 infants/toddlers and nine pregnant women who visited the Posyandu. The examination revealed that 48% of infants and toddlers were at risk of stunting (short and very short stature), and 11.1% of pregnant women had anaemia. Thus, early detection of stunting through the online KMS application facilitates data interpretation so that it can provide information quickly and recommend further treatment to mothers to achieve ideal child height growth. In addition, early detection of anaemia can prevent stunting in children.